Support actions undertaken for the woman by companions in public maternity hospitals - Carolina Frescura Junges; Odaléa Maria Brüggemann; Roxana Knobel; Roberta Costa (Universidade de São Paulo, 2018)
ABSTRACT Objective: to identify the support actions undertaken for the woman during labor, birth, cesarean section and the postpartum period. Method: a transversal study, undertaken in three public maternity hospitals, with a sample of 1,147 companions. The data were collected through interviews and were analyzed using descriptive statistics. The support actions were classified in four dimensions: emotional, physical, informational and relating to intermediation. Results: the majority of interviewees were the partner/father of the baby (76.7%). In labor, birth and the postpartum period, the actions of emotional support - such as calming, encouraging and praising, were performed by more than 80.0% of the companions; informational support, by approximately 70.0%; and intermediation by fewer than 65.0% of them. In childbirth, the emphasis on physical support was observed in assisting with walking (84.4%), and in changing position (90.4%). Conclusion: the companions participate actively in the birth process, performing actions of support in the four dimensions. Emotional support is the most frequent, followed by physical and informational support, mainly during labor and birth. The results contribute to valuing the companion from the woman's social network in the birth scenario and to the recognition of his/her role as a provider of support.